PERANCANGAN KATALOG DIGITAL PRODUK FURNITURE ALIZETTI BERBASIS WEBSITE - Fitro Nur Hakim; Nur Rokhman (CV. Denasya Smart Publisher, 2024)
A product catalog website is a marketing and promotional medium that can be used by Small and Medium Enterprises to expand market share and increase competitiveness in the era of global competition. This research aims to design a website for the Alizetti Semarang furniture product catalog, using the Five Stage Model development method. The designed website has elegant design characteristics, can adapt to various user laptop screen resolutions. The research results show that the furniture product catalog website can increase the knowledge and capabilities of Alizetti Business in utilizing information and communication technology, as well as maintaining relationships with customers and increasing market potential. It is hoped that this furniture product catalog website can be an example for other businesses in Indonesia to develop their business online or website-based.